Natural Host Relationships and Genetic Diversity of Rodent-Associated Hantaviruses in Southeastern Brazil - Moro de Sousa, Ricardo Luiz; Moreli, Marcos Lazaro; Borges, Alessandra Abel; Campos, Gelse Mazzoni; Livonesi, Marcia Cristina; Moraes Figueiredo, Luiz Tadeu; Pinto, Aramis Augusto [UNESP] (Karger, 2008)
Objective: Hantaviruses are rodent-borne RNA viruses that have caused hantavirus cardiopulmonary syndrome in several Brazilian regions. In the present study, geographical distribution, seroprevalence, natural host range, and phylogenetic relations of rodent-associated hantaviruses collected from seven counties of Southeastern Brazil were evaluated. Methods: ELISA, RT-PCR and phylogenetic analysis were used in this study. Results: Antibodies to hantavirus were detected in Bolomys lasiurus, Akodon sp. and Oligoryzomys sp., performing an overall seroprevalence of 5.17%. All seropositive rodents were associated with grasslands or woods surrounded by sugar cane fields. Phylogenetic analysis of partial S- and M-segment sequences showed that viral sequences isolated from B. lasiurus specimens clustered with Araraquara virus. However, a sequence from Akodon sp. shared 100% similarity with Argentinian/Chilean viruses based on the partial S- segment amino acid sequence. Conclusion: These results indicate that there are associations between rodent reservoirs and hantaviruses in some regions of Southeastern Brazil, and suggest the existence of additional hantavirus genetic diversity and host ecology in these areas. Copyright (C) 2008 S. Karger AG, Basel
Keywords: Hantavirus; Sigmodontine rodent; ELISA; Seroprevalence; RT-PCR; Sequencing phylogenetic reconstruction